Power management in microgrid operation - Seah, Kelvin Kuan Joo (2014)
Oil and natural gas are deleting in unprecedented rate in our growing economy. As global warming and raising oil prices push our existence into disrepute, many have turned to nuclear energy for many years to fill this need. Though nuclear disasters happened in the past; it was the most recent outbreak at Japan’s Fukushima nuclear power station in 2011 that gotten many countries to reconsider the continuing use of nuclear energy.